Linking Community Literacies to critical literacies through community language and literacy mapping. (January 2020) - López, Minda Morren
Abstract: In this study, teachers engaged in Community Language and Literacy mapping to understand the resources present in their communities in urban, rural, and suburban schools. Through the ethnographic project, teachers built on their findings to create critical literacies units. As a result, teachers embraced complexity and considered multiple perspectives. However, many found it difficult to push their students to action and social justice. Overall participants broadened their view of what counts as literacy, deepened their understanding of critical literacies, and used community language and literacy practices in their classroom teaching. Highlights: Community mapping expanded teachers' views of what counts as literacy(ies). Through community mapping teachers shed deficit perspectives of their communities. Connecting critical literacies units to community mapping was key for teacher learning. Teachers reflected that critical literacies were not as difficult as they initially thought.